Pengembangan Dan Uji Validitas Soal-Soal Kemampuan Pemahaman Konsep Pada Materi Soal Himpunan - Aulia Sefti Rahmadhani; Selvia Erita (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Understanding concepts is very important in learning mathematics, because with a thorough understanding, students can solve a problem and are able to apply this learning to the real world. This research aims to develop and test the validity of conceptual understanding ability questions on set question material in Class VIID MTsN 2 Kerinci. This type of research uses development research. The research subjects were class VII D students consisting of 26 students. The data collection techniques used were tests, interviews and documentation. The results of the research show that students have a very good understanding of concepts. It can be seen from the results of the analysis of the test question data that it can be seen that there are 8 students (22.9%) included in the category of having the ability to understand concepts very well, 5 students (14.3%) included in the category of having the ability understanding of the concept was good, 7 students (20.0%) were in the sufficient category, and 5 students (14.3%) were in the poor category. This means that overall there are 8 students out of 25 students who have the ability to understand concepts in the very good category. This shows that set material questions have a potential effect on students' ability to understand concepts.